Sex influence on kinematics parameters for elite swimmers - Baly, L.; Chavet, P.; Berton, E.; Favier, D. (2002)
The aim of this study is to quantify specific differences in the motion between the two sexes for an elite finswimmers population. Similar studies [1] have shown that differences indeed exist in swimming for all swimming style and race distance. Consistently with previous research works [2], kinematics analysis in real situation was used to evaluate the different relevant parameters.